Psychological intervention reduces self-reported performance anxiety in high school music students - Braden, Alice M.; Osborne, Margaret S.; Wilson, Sarah J. (Frontiers in Psychology, 2015)
Music performance anxiety (MPA) can be distressing for many young people studying music, and may negatively impact upon their ability to cope with the demands and stressors of music education. It can also lead young people to give up music or to develop unhealthy coping habits in their adult music careers. Minimal research has examined the effectiveness of psychological programs to address MPA in young musicians. Sixty-two adolescents were pseudo-randomized to a cognitive behavioral (CB) group-delivered intervention or a waitlist condition. The intervention consisted of psychoeducation, cognitive restructuring and relaxation techniques, identification of strengths, goal-setting, imagery and visualization techniques to support three solo performances in front of judges. Significant reductions in self-rated MPA were found in both groups following the intervention and compared to their baseline MPA. This reduction was maintained at 2-months follow-up. There appeared to be inconsistent effects of the intervention upon judge-rated MPA, however the presence of floor effects precluded meaningful reductions in MPA. There appeared to be no effect of the intervention upon judge-rated performance quality. This study highlights the potential for group-based CB programs to be delivered within school music curricula to help young musicians develop skills to overcome the often debilitating effects of MPA.